Porcine acellular lung matrix for wound healing and abdominal wall reconstruction: A pilot study - Fernandez-Moure, Joseph S (J Tissue Eng, 2016)
Surgical wound healing applications require bioprosthetics that promote cellular infiltration and vessel formation, metrics associated with increased mechanical strength and resistance to infection. Porcine acellular lung matrix is a novel tissue scaffold known to promote cell adherence while minimizing inflammatory reactions. In this study, we evaluate the capacity of porcine acellular lung matrix to sustain cellularization and neovascularization in a rat model of subcutaneous implantation and chronic hernia repair. We hypothesize that, compared to human acellular dermal matrix, porcine acellular lung matrix would promote greater cell infiltration and vessel formation. Following pneumonectomy, porcine lungs were processed and characterized histologically and by scanning electron microscopy to demonstrate efficacy of the decellularization. Using a rat model of subcutaneou implantation, porcine acellular lung matrices (n = 8) and human acellular dermal matrices (n = 8) were incubated in vivo for 6 weeks. To evaluate performance under mechanically stressed conditions, porcine acellular lung matrices (n = 7) and human acellular dermal matrices (n = 7) were implanted in a rat model of chronic ventral incisional hernia repair for 6 weeks. After 6 weeks, tissues were evaluated using hematoxylin and eosin and Masson’s trichrome staining to quantify cell infiltration and vessel formation. Porcine acellular lung matrices were shown to be successfully decellularized. Following subcutaneous implantation, macroscopic vessel formation was evident. Porcine acellular lung matrices demonstrated sufficient incorporation and showed no evidence of mechanical failure after ventral hernia repair. Porcine acellular lung matrices demonstrated significantly greater cellular density and vessel formation when compared to human acellular dermal matrix. Vessel sizes were similar across all groups. Cell infiltration and vessel formation are well-characterized metrics of incorporation associated with improved surgical outcomes. Porcine acellular lung matrices are a novel class of acellular tissue scaffold. The increased cell and vessel density may promote long-term improved incorporation and mechanical properties. These findings may be due to the native lung scaffold architecture guiding cell migration and vessel formation. Porcine acellular lung matrices represent a new alternative for surgical wound healing applications where increased cell density and vessel formation are sought.